Who Doesn't Want to be Vaccinated? : Determinants of Vaccine Hesitancy During COVID-19 - Khan, Hibah (IMF Working Papers; Working Paper, 2021)
Quick vaccine rollouts are crucial for a strong economic recovery, but vaccine hesitancy could prolong the pandemic and the need for social distancing and lockdowns. We use individual-level data from nationally representative surveys developed by YouGov and Imperial College London to empirically examine the determinants of vaccine hesitancy across 17 countries and over time. Vaccine demand depends on demographic features such as age and gender, but also on perceptions about the severity of COVID-19 and side effects of the vaccine, vaccine access, compliance with protective behaviors, overall trust in government, and how information is shared with peers. We then introduce vaccine hesitancy into an extended SIR model to assess its impact on pandemic dynamics. We find that hesitancy can increase COVID-19 infections and deaths significantly if it slows down vaccine rollouts, but has a smaller impact if all willing adults can be immunized rapidly.